Rethinking Conflict Management Strategies in Nigeria: A Critical Review of the MEND Amnesty - Henry, Jacob Uche; Amiara, Amiara Solomon; Odeke, Francis (EBSU Journal of Social Sciences and Humanities, 2021)
Since the declaration of amnesty in 2009 by Nigerian government as a strategy for resolving the Niger Delta crisis, violence has only declined but has not disappeared. Many state officials attribute this relative calm to the amnesty programme whereas, analysts and scholars alike see it as a temporal suppression of violence through cash incentives. It is against this backdrop, therefore, that this paper seeks to critically and holistically explore the events and terms embedded in the 60-day ceasefire truce between the federal government of Nigeria and the Movement for the Emancipation of the Niger Delta (MEND) militants which provided the negotiating platform that led to the current amnesty and integration programmes. The paper argues that the Niger Delta conflict has continued despite the amnesty declaration because both the government and the militants failed to satisfy some of the conditions of the peace agreement. In this, the paper recommends that both parties in conflict and other stakeholders should reengage in multilateral dialogue to address those issues captured in the amnesty deal.